The Effect of Adhesive Concentration on The Characteristics of Charcoal Briquettes From Bamboo Betung (Dendrocalamus asper Backer) - Raushan Alfikri; Fakhruzy Fakhruzy (Journal of Global Sustainable Agriculture, 2024)
Biomass is a sustainable alternative energy source to meet increasing energy needs, amidst limited conventional energy reserves. One use is through the production of charcoal briquettes. Betung bamboo (Dendrocalamus asper Backer) is a potential biomass raw material for making charcoal briquettes because it has high lignin and holocellulose content, as well as the ability to grow quickly. The aim of the research was to examine the effect of adhesive concentration on the characteristics of charcoal briquettes from betung bamboo (Dendrocalamus asper Backer) on water content, density, burning rate test, volatile matter content, content and bound carbon content. The method used was a Completely Randomized Design (CRD) which consisted of three treatments and five replications, with adhesive concentration levels of 5%, 10% and 15%. The test results produced an average value of water content of 7.50% - 9.85%, density of 0.67 - 0.77 gr/cm³, combustion rate of 0.11 - 0.18 gr/minute, volatile matter content of 2.66 % - 4.52%, ash content 30.86% - 32.99%, and bound carbon content 55.03% - 56.85%. These results meet SNI 01-6235-2000 standards, especially in testing density, volatile matter content and water content with an achievement percentage of 95%.